2015
DOI: 10.1007/s12517-015-2038-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil-water characteristic curves and hydraulic conductivity of nanomaterial-soil-bentonite mixtures

Abstract: This study evaluates the influence of nanomaterials (nano-copper and nano-alumina) on the suction and hydraulic conductivity of compacted soil-bentonite mixture with different plasticity indexes. The soil suction and hydraulic conductivity of the compacted soil-bentonite mixtures were measured before and after the addition of nanomaterials. Soil-water characteristic curves were then developed for compacted soil samples (with and without nanomaterial) using a pressure membrane apparatus. It was found that satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…The improved performance of Oltu clay, aluminum oxide, and iron oxide in reducing permeability can be explained by the increased packing density due to their smaller size, as well as their structural properties. Results similar to those suggesting that smaller-diameter nanomaterials reduce the permeability more reported in this study dan be found in Bahmani et al [36] and Taha and Taha [37].…”
Section: Permeabilitysupporting
confidence: 92%
“…The improved performance of Oltu clay, aluminum oxide, and iron oxide in reducing permeability can be explained by the increased packing density due to their smaller size, as well as their structural properties. Results similar to those suggesting that smaller-diameter nanomaterials reduce the permeability more reported in this study dan be found in Bahmani et al [36] and Taha and Taha [37].…”
Section: Permeabilitysupporting
confidence: 92%
“…Table 2 shows the physical and engineering properties of Salak Tinggi residual soil. The result shows that the average specific gravity for Salak Tinggi residual soil is 2.67 and these values show the similarities when compared with previous studies of sedimentary residual soil [2,18,19]. The residual soil specific gravity values are varies at each location depending on the mineralogy of soil and the history of weathering at any specific site.…”
Section: Methodssupporting
confidence: 67%
“…Taipodia et al (2011) reported that the hydraulic conductivity of the clay (2.41 Â 10 À5 ) decreased to 1.25 Â 10 À5 cm/s as a result of the addition of nano CaO to the clay, and this result was related to the filling of soil voids with nanoparticles (Taipodia et al 2011). Taha & Taha (2016) reported that the hydraulic conductivity decreased in general as a result of the addition of nano-alumina and nano copper to the soil samples containing 20% bentonite, and nano-alumina performed better than nano copper in terms of reducing the hydraulic conductivity (Taha & Taha 2016).…”
Section: Impermeability Methods Applied In Landfill Areasmentioning
confidence: 99%